1995
DOI: 10.1007/bf02220435
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of upper gastrointestinal hemorrhage in patients with hepatocellular carcinoma

Abstract: Our purpose was to determine, in a prospective study, the causes of gastrointestinal hemorrhage in patients with hepatocellular carcinoma, and the relationship of portal vein invasion with variceal hemorrhage in these patients. During an 11-month period, 55 patients presented with hepatocellular carcinoma presented with signs and/or symptoms of upper gastrointestinal hemorrhage. Forty-seven percent had bleeding from varices, whereas the majority, 53%, had a nonvariceal bleeding source. Among those with nonvari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…These specific features of HCC mean that it rarely infiltrates the gastrointestinal (GI) tract directly. The incidence is reported to be 0.5% to 2% of clinical HCC cases [1,2] . Whether such an invasion causes massive hemorrhage or obstruction, a complete en bloc resection of these extensive HCCs can be safely performed using modern surgical techniques and sophisticated perioperative management.…”
Section: Introductionmentioning
confidence: 99%
“…These specific features of HCC mean that it rarely infiltrates the gastrointestinal (GI) tract directly. The incidence is reported to be 0.5% to 2% of clinical HCC cases [1,2] . Whether such an invasion causes massive hemorrhage or obstruction, a complete en bloc resection of these extensive HCCs can be safely performed using modern surgical techniques and sophisticated perioperative management.…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study, Chen et al [12] reported 8 out of 396 patients (2%) with HCC who developed gastrointestinal involvement during the course of the disease. Lin et al [2,[6][7][8][9][10][11][12] similarly reported gastrointestinal metastases in 11 out of 2237 patients with HCC (0.5%). Only 10 cases of HCC invading directly into the stomach could be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 10 cases reported [2,[6][7][8][9][10][11][12] , 6 had received some form of regional therapy, such as trans-arterial chemoembolization (TACE), intra-arterial chemotherapy or radiotherapy, either alone or in combination, prior to the HCC invading the gastro-intestinal tract. This includes 4 of the 5 patients with direct invasion of the gastrointestinal tract by contiguous HCC reported by Chen et al [12] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations